Physical Environment and Its Influence on Asthenopia: A Cross-Sectional Study among Batik Artisans in Klaten Regency, Indonesia - Putri, Cita Fitria; Astutik, Risa Septi; Setyaningsih, Yuliani (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: Asthenopia, or eye strain, is a prevalent issue among batik artisans in Klaten Regency, Indonesia, due to the visually demanding nature of their work and potentially suboptimal working conditions.Methods: This cross-sectional study investigated the influence of physical environmental factors, specifically lighting intensity, temperature, and humidity, on the occurrence of asthenopia symptoms among 155 female batik artisans. Data were collected through interviews using the Visual Fatigue Index questionnaire and environmental measurements.Results: Most participants (65.8%) experienced asthenopia symptoms, with an average score of 0.47 (SD ±0.15). The most common symptoms included watery eyes, stinging sensations, gritty feelings, difficulty focusing, and heavy sensations in the eyes. Spearman's rank correlation revealed a statistically significant association between ambient temperature and asthenopia complaints (p = 0.009), while no significant correlations were found for lighting intensity (p = 0.799) and humidity (p = 0.742). The average workplace temperature was 28.61°C (SD ±1.04), exceeding the recommended comfort range of 23–26°C. Although 81.9% of participants worked under lighting levels below the recommended 300 lx, this factor was not significantly associated with asthenopia.Conclusion: These findings highlight the importance of improving thermal comfort in traditional batik workplaces to reduce visual strain among artisans. Further research employing longitudinal and objective methodologies is recommended to better understand the complex interplay between environmental and individual factors contributing to asthenopia in this population.